2018
DOI: 10.1016/j.orgel.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Electron mobility of non-fullerene acceptors using a time of flight method

Abstract: Organic solar cells are a promising renewable energy technology, offering the advantages of mechanical flexibility and solution processability. The charge carrier mobility is an important parameter as it influences the competition between charge extraction and recombination and therefore the cell efficiency. We report the electron mobility of two high performance non-fullerene acceptors ITIC and IDTBR in neat films and blended with their common donors. In a pure film ITIC has a zero-field electron mobility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…29 On the other hand, 3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2 0 ,3 0 -d 0 ]-s-indaceno[1,2-b:5,6-b 0 ]dithiophene (ITIC) and its methyl derivative (ITIC-M) have been intensively studied in combination with low-bandgap polymers due to their high performance (beyond 12%). 10 When ITIC was blended with P3HT, however, the system resulted in very low electron mobility 30 and PCEs below 2%. 31 Besides the device performance, a theoretical study on colour tuning recently revealed that NFAs are the best approach to tune the aesthetic appearance (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…29 On the other hand, 3,9-bis(2-methylene-(3-(1,1-dicyanomethylene)-indanone))-5,5,11,11-tetrakis(4-hexylphenyl)-dithieno[2,3-d:2 0 ,3 0 -d 0 ]-s-indaceno[1,2-b:5,6-b 0 ]dithiophene (ITIC) and its methyl derivative (ITIC-M) have been intensively studied in combination with low-bandgap polymers due to their high performance (beyond 12%). 10 When ITIC was blended with P3HT, however, the system resulted in very low electron mobility 30 and PCEs below 2%. 31 Besides the device performance, a theoretical study on colour tuning recently revealed that NFAs are the best approach to tune the aesthetic appearance (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the electron mobility is about an order of magnitude higher than most other NFAs reported recently. [30][31][32] The carrier recombination lifetime, obtained from photoinduced absorption (PIA) measurements 33 at the open circuit condition (Fig. 7), is 9.8×10 -6 s. It should be noted that the open circuit condition is relevant in this case since carrier diffusion in the neutral region of the active layer is being considered.…”
Section: Resultsmentioning
confidence: 98%
“…[8] In a study comparing ToF mobilities of two NFAs, O-IDTBR and ITIC, the authors were unable to achieve thick enough O-IDTBR films and therefore only blend mobilities could be compared. [8] Similarly, only blend mobilities can be compared when using Photo-CELIV, which determines mobility directly from OPV devices. For performing a comparison of NFA mobilities a technique which determines the mobility of a single component rather than a blend is preferable.…”
Section: Introductionmentioning
confidence: 99%
“…One drawback of ToF is that it requires film thicknesses of around a micrometer. For neat NFAs such thicknesses are not always achievable, mainly due to low solution viscosities for deposition . In a study comparing ToF mobilities of two NFAs, O‐IDTBR and ITIC, the authors were unable to achieve thick enough O‐IDTBR films and therefore only blend mobilities could be compared .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation